Stigma Sosial dan Perundungan Siber Terhadap Pembuat Konten Perempuan Dalam Pernikahan Campuran - Magvira Yuliani; Sri Mustika (JURNAL KOMUNIKATIO, 2025)
Globalization and advances in communication technology have driven profound socio-cultural changes by intensifying cross-cultural interactions within digital spaces, to the point of blurring geographical boundaries. One clear manifestation of these changes is the growing prevalence of mixed or transnational marriages. Social media plays a pivotal role in constructing narratives of cross-cultural romance, yet it simultaneously provides a platform for social stigma and cyberattacks, particularly targeting Indonesian female content creators in mixed marriages. This study seeks to examine the various forms of stigma and online harassment they encounter, employing a netnographic observational approach, literature review, and theoretical frameworks drawn from symbolic interactionism, critical discourse analysis, and agenda-setting theory. The findings reveal that these female content creators frequently become targets of gender-based hate speech, nationalistic stereotypes, and recurring, organized racist attacks. Such patterns reflect the persistence of cultural and patriarchal biases that have migrated into digital spaces. Inadequate systemic support forces these women to rely on individual self-protection strategies. Consequently, this study highlighted the need to promote digital literacy, foster social empathy, and strengthen legal protections to build a safer and more equitable digital environment for women in mixed marriages, who hold significant potential to serve as bridges for inclusive cultural exchange.